2008
DOI: 10.1097/jom.0b013e318162f628
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Weight Loss and Blood Pressure Control at Work: Impact of an Education and Intervention Program

Abstract: A targeted worksite intervention program may be an effective way to lower BP and promote exercise and weight loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
68
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(73 citation statements)
references
References 45 publications
4
68
0
1
Order By: Relevance
“…The baseline survey response suggested that the study group lacked the nutrition knowledge necessary to make healthy food choices. Our findings are consistent with others that have shown that educational approaches focused on nutrition and physical activity can effectively increase healthy behaviors, achieve clinically significant weight loss [50] and improve blood pressure during the intervention and at the one-year follow-up [17].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The baseline survey response suggested that the study group lacked the nutrition knowledge necessary to make healthy food choices. Our findings are consistent with others that have shown that educational approaches focused on nutrition and physical activity can effectively increase healthy behaviors, achieve clinically significant weight loss [50] and improve blood pressure during the intervention and at the one-year follow-up [17].…”
Section: Discussionsupporting
confidence: 81%
“…Health promotion and public health advocates have identified the workplace as a promising setting for addressing excessive adiposity and chronic disease risk [17]. Evidence from best practices recommends that weight management interventions should include health professional-facilitated education and tailored feedback, a work environment that supports behavior changes, and employee involvement in the intervention [19,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Relatively few previous worksite intervention studies included an assessment of cardiovascular disease risk factors over a long period of time (Aldana et al, 2005;Engbers et al, 2007;Gemson et al, 2008;Glasgow et al, 1995Glasgow et al, , 1997Naito et al, 2008;Nilsson et al, 2001;Shimizu et al, 2004), even fewer were conducted in the United States (Aldana et al, 2005;Gemson et al, 2008;Glasgow et al, 1995Glasgow et al, , 1997, and the results were sometimes negative (Glasgow et al, 1995(Glasgow et al, , 1997, despite careful study designs and large sample sizes. One important difference between studies that may help to explain the discrepant findings is that the larger Take Heart trials (Glasgow et al, 1995(Glasgow et al, , 1997 involved numerous worksites, with high variability between worksites in terms of response to the interventions, and their analysis was at the level of the worksite rather than the individual.…”
Section: Discussionmentioning
confidence: 99%
“…Several worksite programs included an evaluation of cardiovascular disease risk factors, some of which lasted more than 6 months (Engbers et al, 2007;Gemson et al, 2008;Glasgow et al, 1995Glasgow et al, , 1997Naito et al, 2008), but the results were variable. In the present study, we implemented a novel, 1-year worksite intervention called "Worksite Opportunities for Wellness" (WOW) among medical center employees and compared it to an assessment only condition that included personalized health reports.…”
Section: Introductionmentioning
confidence: 99%